A new species of the fish louse genus Dipteropeltis Calman, 1912 (Crustacea: Branchiura) from Peru - Gaboardi, Lyra M.; Reeves, Lawrence E.; Morey, Germán Augusto Murrieta; Stanton, Daniel L.; Carney, Ryan M. (Zootaxa, 2023)
Dipteropeltis is a poorly described genus of fish louse endemic to South America. In a small blackwater region within Loreto, Peru, 13 adult and juvenile specimens of an unidentified species of Dipteropeltis Calman, 1912, as well as one adult specimen of D. hirundo Calman, 1912, were observed and collected. Scanning electron and light micrographs were acquired to examine and measure key features of these specimens. Morphological differences from the two known species of Dipteropeltis, D. hirundo and D. campanaformis Neethling et al., 2014, indicate that the collected specimens represent a new species. Dipteropeltis longicaudatus sp. nov. is diagnosed by elongate abdominal lobes, a chevron-shaped carapace, and uniquely shaped maxillae. One specimen represents the longest branchiuran documented to date at 31.5 mm. Additionally, we provide the first sequence data for this genus using DNA barcoding, which corroborates our designation of a new species. Videos were also captured that document behaviors including host attachment, pulsating abdominal lobes, suction disc “walking”, and swimming. Findings have implications for its teleost hosts, Triportheus albus Cope, 1872 and Brycon amazonicus Spix & Agassiz, 1829, the latter being a critical species for aquaculture and commercial fisheries in Amazonia.